Quantifying the Reporting, Coverage and Consistency of Key Indicators in Mangrove Restoration Projects - Gatt, Yasmine M.; Andradi-Brown, Dominic A.; Ahmadia, Gabby N.; Martin, Philip A.; Sutherland, William J.; Spalding, Mark D.; Donnison, Amy; Worthington, Thomas A. (Frontiers in Forests and Global Change, 2022)
Mangroves are often cleared for aquaculture, agriculture, and coastal development despite the range of benefits for people and nature that they provide. In response to these losses, there are multiple global and regional efforts aimed at accelerating mangrove forest restoration, resulting in many restoration projects being implemented and managed by different groups with highly diverse objectives. The information reported from these restoration projects is extremely variable, limiting our ability to identify whether desired objectives have been met or key factors that determine effective and durable restoration have been applied. To address this problem, we developed a holistic monitoring framework that captures the key indicators of restoration, spanning project aims, intervention type, costs, and ecological and socioeconomic outcomes. Subsequently, using a systematic literature search, we examined 123 published case studies to identify the range and quality of reported information on restoration relative to our framework. We found that there were many gaps in reporting for multiple indicators. Sections related to site conditions prior to restoration (reported in only 32% of case studies) and socioeconomic outcomes (26%) were consistently missing from most project reporting. Conversely, information on the type of intervention was reported for all case studies, and the aims of the product (reported in 76% of case studies) and ecological monitoring (82%) was far more prevalent. Generally, the restoration literature did not follow any specific framework in terms of reporting what likely contributed to the gaps in the information recorded. These gaps hinder comparisons between case studies, inhibiting the ability to learn lessons from previous restoration attempts by identifying commonalities. The need for more structure and consistent reporting supports the development of a standard restoration tracking tool that can facilitate the comparison of restoration efforts, aiding the implementation of future projects.